Association between emergency department length of stay and adverse perioperative outcomes in emergency surgery: A cohort study in two Colombian University hospitals (2019)
Background: In low- and middle-income countries emergency surgery represents a higher proportion of the total number of surgeries and is associated with greater morbidity/mortality. Study aims were to determine if emergency department length of stay (ED-LOS) was associated with adverse perioperative outcomes and if such association varied across patient's risk categories. Methods: A retrospective cohort study was conducted of adult patients who underwent orthopedic or abdominal emergency surgery at two Colombian University hospitals. The population comprised a mix of a representative sample of eligible cases, with unselected patients (2/3), enriched with a high-risk subset (1/3). ED-LOS was defined as the interval between emergency department arrival and surgery start time. Our primary outcome was an adverse perioperative outcome during hospitalization, which was a composite of in-hospital mortality or severe complications such as major cardiovascular adverse events, infection, renal failure and bleeding. Results: Among 1487 patients analyzed, there were 519 adverse perioperative outcomes including 150 deaths. In the unselected sample (n = 998) 17.9% of patients presented an adverse perioperative outcome with a mortality of 4.9%. The median ED-LOS was 24.6 (IQR 12.5-53.2) hours. ED-LOS was associated with age, comorbidities and known risk factors for 30-day mortality. Patients developing an adverse perioperative outcome started surgery 27.1 h later than their counterparts. Prolonged ED-LOS increased the risk of an adverse perioperative outcome in patients without risk factors (covariate-adjusted OR = 2.52), while having 1-2 or 3+ risk factors was negatively associated (OR = 0.87 and 0.72, respectively, p less than 0.001 for the interaction). Conclusion: Prolonged ED-LOS is associated with increased adverse perioperative outcome for patients without risk factors for mortality, but seems protective and medically justified for more complex cases. © 2019 The Author(s).